“I remain sincere friend of the Russian Orthodox Church Abroad”. Letters from hieromonk Vasily (Rodzianko) to protopresbyter Georgy Grabbe - Andrey Kostryukov (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. II, Istorii͡a︡, istorii͡a︡ Russkoĭ pravoslavnoĭ t͡s︡erkvi, 2022)
This article makes public the letters of Revd. Vladimir Rodzianko (Hieromonk Vasily) to Protopresbyter Georgy Grabbe. Both the sender and the addressee are wellknown. The former is the future bishop and a long-term prsenter of Orthodox programmes on BBC Radio. The former also became a bishop, and for many years was the secretary of the Synod of Bishops of the Russian Church Abroad having a great infl uence on its policy. The letters were written in the early 1979 in the moment of great changes in the life of their author. The fi rst letter was prepared when he was Protopriest Vladimir, the second soon after his becoming a monk as Hieromonk Vasily. The reason for the letters were the attacks of the administration of the Russian Church Abroad against Moscow Patriarchate as well as the idea, popular in the Russian Orthodox Church, that there is no holy grace at all in any communities not belonging to the Orthodox Church. This idea was put forward by Protopresbyter G. Grabbe in the article Acribeia and Oeconomy. This approach was aggravated by the fact that the administration of the Russian Church Abroad regarded as apostate the clergy of Moscow Patriarchate. The consequence was an idea about their gracelessness. Hieromonk Vasily (Rodzianko) thought that this was erroneous and dangerous. Using certain historical evidence and an opinion of St. Ioann (Maksimovich), he claimed that the Orthodox gaith and the Eucharist are supreme over the jurisdictional controversies and that the temporary discord does not aff ect grace. The letters contain interesting facts as to relations between the Russian Church Abroad and the Serbian Church in the 1920s — 1940s, describe little-known details between the Russian Church Abroad and other branches of Russian church in exile.